Investigation for mechanical properties of dissimilar friction stir welded joints of AA5083 and pure Cu. (2022) - Ghangas, Gyander; Goyat, Vikas; Sirohi, Sachin; Sharma, Satish Kumar; Dhull, Sunil
Abstract: The invention of solid-state welding procedure assimilated as friction stir welding (FSW) has provided an opportunity for industry and scientists to join the non-weldable soft alloys with higher efficiency. FSW is a green and energy-efficient welding process that also makes it possible to weld dissimilar materials effectively with higher joint efficiency. Parameters of the process play an important role in deciding the effectiveness of the FSW process. The present work is an attempt to analyze the effects of rotational speed of tool (RS) on different mechanical characteristics of dissimilar FSWed joints of AA 5083 and pure copper. The RS was varied at three different levels i.e. 800, 1200 and 1600 RPM, where other parameters were kept constant. The results shows that mechanical strength is significantly affected by the variation of RS further, 1200 RPM was observed as optimum value of RS with maximum mechanical strength.